Simulating boundary‐layer rolls with a numerical weather prediction model. (24th September 2015) - Thurston, William; Fawcett, Robert J. B.; Tory, Kevin J.; Kepert, Jeffrey D.
Abstract : Boundary‐layer rolls have an impact on bushfires, pollution dispersion, the triggering of extreme convective weather events, the air–sea interaction and intensification of tropical cyclones and momentum, particle and gas fluxes. Previous numerical modelling studies that investigate the effects of boundary‐layer rolls and the processes that control their dynamics have relied upon high‐resolution, idealised simulations. Recently, however, numerical weather prediction (NWP) systems have increased in horizontal resolution to the point at which they are capable of explicitly resolving shallow convective circulations. Therefore, there is a need to assess the ability of NWP to accurately forecast the formation, development and breakup of boundary‐layer rolls. Here, we assess the ability of the UK Met Office Unified Model (UM), the NWP component of the Australian Community Climate and Earth‐System Simulator (ACCESS), to simulate the life cycle of boundary‐layer rolls. A suite of simulations is performed, over a range of horizontal resolutions, of boundary‐layer rolls observed across Victoria, Australia, on Black Saturday, 7 February 2009. In this case, it is found that a horizontal grid spacing of less than 0.6 km is required to adequately reproduce the scale and evolution of the observed rolls. We note that the boundary layer was particularly deep on this day and as a consequence the boundary‐layer rolls were wider than may be typically observed, meaning the grid spacing specified here lies at the upper end of what would be required with a shallower boundary layer. The model output is used to assess how the boundary‐layer rolls contribute to the high fire danger on Black Saturday. It is suggested that boundary‐layer rolls may increase fire danger by (i) causing wind‐direction variability at the surface, which increases the rate of spread of fires; and (ii) enhancing the process of long‐range spotting by augmenting the vertical lofting of embers.